Synthesis and Evaluation of Novel N‐Cycloheptyl‐Substituted ‐2,3‐ Dihydro‐1,3‐ Benzothiazole‐2‐Carboxamide Targeting the Estrogen Binding Receptor - Bhole, Ritesh; Zambare, Yogesh; Bonde, Chandrakant (Jordan Journal of Pharmaceutical Sciences, 2019)
Bladder cancer is one of the deadly cancer with 16,390 deaths in 2015-16 alone and 76,960 new cases. The matter of concern is more severe with very limited options of treatment and lack of new drugs, cisplatin and doxorubicin are the only two drugs mostly used in therapy. This situation along with the epidemiological data calls for development of newer better and safer agents. Herein, we report nine novel benzothiazole derivatives based on structure based drug discovery and molecular modelling approach. Newly designed compounds were synthesised following four step reaction and were characterized for structural confirmation. These novel compounds were evaluated on the MTT assay for there in vitro efficiency using the TCP1020 cell lines. These were further analysed for their mechanism of action based on in silico studies.Two compounds of the series exhibits promising results which are in agreement with the in silico studies. It was found that the methyl group at seventh position to the nitrogen decreases the electron affinity of the series and is thus responsible for the activity in 4e. The fluorosubstituted compound 4i shows the highest activity with an IC50 of 7.8 in activity of the halogen substituted derivatives.